Arrecadação de bem vago como instrumento urbanístico eficaz na proteção do patrimônio histórico – cultural do município de Manaus. - Carvalho, Ellen Larissa Frota De (2016)
The Legal Relevance of Cultural Heritage came with a adoption unitary and systemic conception of the Constitution of 1988 entered cultural right in the role of environmental. Faced with this importance, the study aims to analyze a new and protection form in cultural through civil institute vague collection, derives from "abandonment", property loss mode, the article 1275, III and 1.276 are Civil Code. With so, work will talk about property law, since any action directed to the good of historical and cultural value preservation interfere directly in this law conforms it to reason with a social function of property. Also, as studied issues on administrative supervision of cultural heritage, as well as the protection of constitutional instruments to brazilian cultural heritage. However, raises the possibility of well abandoned storage as another form of protection. The dissertation method and deductive and data collection technique and the bibliographical research.